Oceanarium Di Bintan Berbasis Recreation, Education, And Conservation Dengan Pendekatan Arsitektur Metafora - Mifthahir Rachman; Wahyu Hidayat; Andre Novan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The strategic location of Indonesia's seas makes potential of marine in Indonesia very high, if this is not accompanied by education about the processing of marine products, eventually it can cause a reduction in marine products from Indonesia. Therefore, a facility is needed to provide information about it which is still recreational. But the rarity of these facilities make the design of the Oceanarium necessary to keep preservation of Indonesia’s sea. Bintan is the right location for this design because the potential of the marine owned is quite high, besides that the tourism sector is also the flagship of Bintan island. So that Bintan can be deserved to be used as the design location. Oceanarium is a facility of recreational education and conservation in the form of a giant marine aquarium located on the edge of the sea. The metaphor’s architectural approach is very suitable with this design of the Oceanarium, because of the nature of the metaphoric architecture which can take the form of certain references so that can describe the function of the Oceanarium from the outside appearance of the building. The research method used includes field data collection and literature study. From the data obtained then it is processed by considering principles of metaphorical architecture. The results of this study design buildings with the concept of